Genome-Wide Identification, Characterization, and Transcript Analysis of the TCP Transcription Factors in Vitis vinifera - Jiu, Songtao; Xu, Yan; Wang, Jiyuan; Wang, Lei; Wang, Shiping; Ma, Chao; Guan, Le; Abdullah, Muhammad; Zhao, Maoxiang; Xu, Wenping; Ma, Wenli; Zhang, Caixi (Frontiers in Genetics, 2019)
The TEOSINTE BRANCHED 1/CYCLOIDEA/ PROLIFERATING CELL FACTORS (TCP) protein, belonging to a plant-specific transcription factors (TFs) family, participates in the control of plant growth and development by regulating cell proliferation. Until now, a comprehensive study of concerning the TCP gene family and their roles in grapevine (Vitis vinifera L.) has not been completed. Using bioinformatics approaches, 17 VvTCP genes were identified and further classified into two classes, designated Class I (PCF subclass) and Class II (CIN and CYC/TB1 subclass), which was further supported by exon-intron organizations and conserved motif analysis. Promoter analysis demonstrated that VvTCPs have numerous cis-acting elements related to plant growth and development, phytohormone and abiotic/ biotic stress responses. The singleton duplication of grapevine TCP genes contributed to this gene family expansion. The syntenic analyses among Vitis vinifera, Arabidopsis, and Oryza sativa showed that these genes located in corresponding syntenic blocks arose before the divergence of V. vinifera, Arabidopsis, and O. sativa. The expression levels of 17 VvTCPs were determined in different tissues and fruit developmental stages, and ABA treatment. 17 VvTCPs exhibited distinct tissue-specific expression patterns, potentially illustrating the functional divergence of VvTCPs in all tested tissues. 11 VvTCPs were down-regulated in five berry developmental stages, while three VvTCPs were up-regulated. Additionally, many members were strongly modulated by ABA treatment, suggesting these VvTCPs have important and diverse regulatory roles in ABA treatment. Our results provide valuable information on the evolution and functions of the VvTCPs, pave the way for further functional verification of these VvTCPs in grapevine.